Implementasi Nilai Integritas dan Profesionalisme Dalam Etika Bisnis Islam Berdasarkan QS. Yusuf Ayat: 55 - Dewi Atika; Khairul Akmal (CV. Ulil Albab Corp, 2026)
This study aims to analyze the implementation of integrity and professionalism values in Islamic business ethics based on QS. Yusuf verse 55. This verse describes the statement of Prophet Yusuf (‘alayhis-salām) who proposed himself as the manager of the state treasury by emphasizing two main characteristics, namely ḥafīẓ (trustworthy) and ‘alīm (knowledgeable). The research method used is a literature review by examining various sources such as the Qur’an, tafsir, books, and scientific journals relevant to the research topic. The results of the study show that integrity in Islam reflects consistency between faith, speech, and actions, which is manifested through honesty, responsibility, and trustworthiness. Meanwhile, professionalism is demonstrated through competence, expertise, and managerial ability in carrying out tasks. QS. Yusuf verse 55 emphasizes that success in economic management and leadership depends not only on technical skills but also on the moral quality of individuals. The implementation of these two values in modern Islamic economics is essential to create a system that is just, transparent, and oriented toward public welfare (maslahah). Therefore, integrity and professionalism serve as the main foundation in building sustainable and ethical Islamic business practices imbued with divine blessings.